Influence of cyclodextrin on the UCST- and LCST-behavior of poly(2-methacrylamido-caprolactam)-co-(N,N-dimethylacrylamide) - Burkhart, Alexander; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2014)
The monomer 2-methacrylamido-caprolactam (4) was synthesized from methacryloyl chloride (3) and racemic α-amino-ε-caprolactam (2). Copolymerization of 4 with N,N-dimethylacrylamide (5) was carried out by a free-radical mechanism using 2,2’-azobis(2-methylpropionitrile) (AIBN) as an initiator. The new copolymers show a lower critical solution temperature (LCST) in water and an upper critical solution temperature (UCST) in ethanol, 1-propanol, and 1-butanol. The solubility properties of the copolymers can be influenced significantly by the addition of randomly methylated β-cyclodextrin (CD). The complexation of the copolymers with CD, was confirmed by the use of ROESY-NMR-spectroscopy.
Keywords: cyclodextrin; LCST; lysine; 2-methacrylamido-caprolactam; UCST